2016
DOI: 10.1007/s10329-016-0512-8
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional adaptation in tempo in pairs of chimpanzees during simultaneous tapping movement: an examination under face-to-face setup

Abstract: Many studies have reported a spontaneous nature to synchronized movement in humans and in non-human primates. However, it is not yet clear whether individuals mutually adapt their movement to each other or whether one individual significantly changes to synchronize with the other. In the current study, we examined a directionality of the tempo adaptation to understand an introductive process of interactional synchrony in pairs of chimpanzees. Four pairs, consisting of five female chimpanzees, produced a finger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Particularly fastacting young chimpanzees in an individual finger-tapping task slowed down their actions when they had to coordinate actions with their slower mothers. 27 Adjusting the speed of actions provides further evidence that the chimpanzees adapt their behavior toward others when walking with them. In addition, when the chimpanzees walked together, the phase relationship values were shorter and showed less variation, suggesting more coordination, compared with when individuals were walking independently (Fisher's test: F = 222.79, df = 84, n = 23, p < 0.001; Figure 4).…”
Section: Coordinated Actions Only In Social Situationsmentioning
confidence: 99%
“…Particularly fastacting young chimpanzees in an individual finger-tapping task slowed down their actions when they had to coordinate actions with their slower mothers. 27 Adjusting the speed of actions provides further evidence that the chimpanzees adapt their behavior toward others when walking with them. In addition, when the chimpanzees walked together, the phase relationship values were shorter and showed less variation, suggesting more coordination, compared with when individuals were walking independently (Fisher's test: F = 222.79, df = 84, n = 23, p < 0.001; Figure 4).…”
Section: Coordinated Actions Only In Social Situationsmentioning
confidence: 99%
“…In the first study conducted under the side-by-side setup, we demonstrated that one chimpanzee gradually matches her tapping movement with auditory cues which was from an interacting partner (Yu & Tomonaga, 2015). In the second study conducted under the face-to-face setup, we found a general tendency on temporal coordination in chimpanzees (Yu & Tomonaga, 2016). These findings indicate that auditory cues can solely facilitate an interaction between chimpanzees but additional visual cues do enhance the influence of an interacting partner's movement on production of one's own movement.…”
Section: Introductionmentioning
confidence: 77%
“…One pair was from kin-relationship, 34-year-old mother [Chloe](GAIN-ID C-0441) and her 14-year-old daughter [Cleo] (GAIN-ID C-0609). Both chimpanzees joined our previous experiments (Yu & Tomonaga, 2015;2016). Another chimpanzee pair was from non-kin relationship, 37-year-old female Pendensa [Pen] (GAIN-ID C-0095) and 38-year-old female [Mari] (GAIN-ID C-0274).…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations